Clinical manifestations and approach to the management of patients with common variable immunodeficiency and liver disease - Daza-Cajigal, Vanessa; Segura-Guerrero, Marina; López-Cueto, María; Robles-Marhuenda, Ángel; Camara, Carmen; Gerra-Galán, Teresa; Gómez-de-la-Torre, Ricardo; Avendaño-Monje, Carmen L.; Sánchez-Ramón, Silvia; Bosque-Lopez, María J.; Quintero-Duarte, Adriana; Bonet-Vidal, María L.; et al. (Frontiers in Immunology, 2023)
Purpose The clinical spectrum of common variable immunodeficiency (CVID) includes predisposition to infections, autoimmune/inflammatory complications and malignancy. Liver disease is developed by a proportion of patients with CVID, but limited evidence is available about its prevalence, pathogenesis and prognostic outcome. This lack of evidence leads to the absence of guidelines in clinical practice. In this study, we aimed at defining the characteristics, course and management of this CVID complication in Spain. Methods Spanish reference centers were invited to complete a cross-sectional survey. Thirty-eight patients with CVID-related liver disease from different hospitals were evaluated by a retrospective clinical course review. Results In this cohort, abnormal liver function and thrombocytopenia were found in most of the patients (95% and 79% respectively), in keeping with the higher incidence of abnormal liver imaging and splenomegaly. The most common histological findings included nodular regenerative hyperplasia (NRH) and lymphocytic infiltration, which have been associated with portal hypertension (PHTN) leading to a poorer prognosis. Autoimmune/inflammatory complications occurred in 82% of the CVID patients that developed liver disease and 52% of the patients treated with immunomodulators showed a reduction in the liver function tests’ abnormalities during treatment. Among the experts that conducted the survey, there was 80% or more consensus that the workup of CVID-related liver disease requires liver profile, abdominal ultrasound and transient elastography. The majority agreed that liver biopsy should be essential for diagnosis. There was 94% consensus that endoscopic studies should be performed in the presence of PHTN. However, there was 89% consensus that there is insufficient evidence on the management of these patients. Conclusion Liver disease varies in severity and may contribute substantially to morbidity and mortality in patients with CVID. Hence the importance of close follow-up and screening of this CVID complication to prompt early targeted intervention. Further research is needed to evaluate the pathophysiology of liver disease in patients with CVID to identify personalized treatment options. This study emphasizes the urgent need to develop international guidelines for the diagnosis and management of this CVID complication.